Prognostic value of the initial chest high-resolution CT pattern in idiopathic pulmonary fibrosis - Le Rouzic, Olivier; Bendaoud, Sofiane; Chenivesse, Cécile; Rémy, Jacques; Wallaert, Benoit (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background. Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial pneumonia with a poor prognosis, and there is a clear need to identify factors predictive of disease progression and survival. Previous studies have suggested that patient survival may be associated with specific features on chest CT. Here, we evaluated the prognostic value of the initial high-resolution CT (HRCT) pattern according to the classification recommended by the most recent guidelines for IPF. Methods. A total of 66 patients diagnosed with IPF between 2000 and 2010 were included in this retrospective study. Patients were classified into three groups based on the pattern of their initial HRCT: definite usual interstitial pneumonia (UIP) (UIPdef n = 26), possible UIP (UIPposs, n = 29), or inconsistent with UIP (UIPincons n = 11). Epidemiological data, functional data, and patient survival were compared. Results. The median survival time was 30, 46, and 107 months for UIPdef, UIPposs, and UIPincons groups, respectively (p = 0.51). Patients with UIPdef pattern HRCT were more likely to be former smokers (p = 0.007) in comparison with UIPincons, to have a lower diffusing capacity of the lung for carbon monoxide in comparison with UIPposs (p = 0.01) and to have a higher estimated systolic pulmonary artery pressure (p = 0.002). Patients with UIPincons pattern HRCT were more likely to be younger (p = 0.004). Conclusion. There were no significant difference in survival between the three patient groups categorized by their initial chest HRCT pattern.